PRAGMATIC ANALYSIS OF EXPRESSIONS INVOLVING HUMAN BODY PARTS IN ENGLISH AND UZBEK LANGUAGES (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article is devoted to the pragmatic analysis of English alternatives of phraseologisms in Uzbek language involving human body parts, such as “bosh/head”, “burun/nose”, “bo’yin/neck”, “ko’z/eye, “foot/oyoq”, “mouth/og’iz”, “tongue/til” and their equivalents are defined.